Tinjauan Kinerja Simpang Tak Bersinyal Terhadap Arus Lalu Lintas Pada Simpang Lima Jalan Labungkari, Kabupaten Buton Tengah Sulawesi Tenggara: Teknik Sipil - Tafakur La Ode, Al; Hidayat, Arman; Tafakur La Ode, Rostiani (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
The Mawasangka-Labungkari axis road is located in the Lakudo District area, Central Buton Regency, and is a Southeast Sulawesi Province. The development of the transportation area is one of the pillars supporting the economy of a region that cannot be separated from regional development, as well as at the Lima Labungakari intersection which is an unsignalized intersection where various types of vehicles pass daily, such as motorbikes, cars, trucks, and so on. This study aims to determine the highest traffic volume, namely on Jalan Poros Lolibu-Mawasangka (Segment A) Sundays at 06.00-18.00 the flow is 777.1 pcu/hour, has the highest current value compared to other roads, and the capacity The Lolibu-Mawasangka axis road (segment A) is 2,401.2 pcu/hour, while the Gersamata road produces a capacity of 1,461.6 pcu/hour, while the Lakapera-Waraa Axle Road (Segment C) produces a capacity of 2,270.7 pcu/hour so that it is suitable with the basic vehicle capacity that has been regulated by MKJI 1997, namely 2,900 per lane 2/2 UD and to find out the degree of saturation (DS) value at this research location is below 0.75, namely in segment A it is 0.25, in segment B it is 0.35 and in segment C it is 0.24, so it can mean that this intersection can still serve the vehicles that pass through it well.